Upaya Meningkatkan Hasil Belajar Kognitif Siswa Pada Pelajaran Termokimia Menggunakan Student Team Achievement Division (STAD) [An Attempt to Improve the Students' Cognitive Learning Result in Thermochemistry by Using the Student Team Achievement Division (STAD)] - Nesa Fiona; Friska Juliana Purba (Universitas Pelita Harapan, 2020)
The Triune God is a God related in love so that students as an image of God are also enabled to relate in class communities. The class as a learning community uses every potential to achieve shared cognitive learning goals. In fact, when studying thermochemical class XI at XYZ Jakarta High School, it was found that students had not used their academic abilities to achieve shared learning goals. Based on their academic abilities students provide different cognitive responses and learning outcomes. Students with high academic ability do not do the practice questions because they feel they understand, and the learning outcomes are good. Low academic ability students give up learning thermochemistry because they find it difficult and their learning outcomes are low. Based on that, this paper will examine efforts to improve student cognitive learning outcomes in thermochemical lessons using the STAD cooperative learning model. Papers are written using literature study data collection techniques. The results showed that STAD can be used to improve student cognitive learning outcomes on thermochemical topics. STAD cooperative learning provides group learning that encourages students to check understanding and exchange information about thermochemistry.